Tissue-specific differential induction of aspartate transcarbamylase by hydrocortisone in rats of various ages - Patnaik S.K.; Patnaik R. (My University, 2025)
The activity and induction pattern of aspartate transcarbamylase (ATCase) of the liver (a mitotic tissue) and heart (a post-mitotic tissue) of rats of various ages were studied. The activity of the enzyme of both tissues was highest in the immature rat and decreased significantly thereafter with increasing age of the animal. Adrenalectomy and hydrocortisone treatments altered the activity of liver ATCase in rats of all the ages. However, these treatments altered the heart enzyme of the immature and adult rats, but not of senescent rat. The magnitude of induction of the enzyme by hydrocortisone was highest in the immature rat. Actinomycin D inhibited the hormone-mediated induction of ATCase is both the liver and heart.